An Analysis Of Personal Selling Strategies And The Physical Environment In Creating Customer Satisfaction: A Qualitative Study of Cikole Luwak Coffee, Lembang: Analisis Strategi Personal Selling Dan Suasana Lingkungan Fisik Dalam Menciptakan Kepuasan Pelanggan: Studi Kualitatif pada Kopi Luwak Cikole, Lembang - Ahmad Ferdiansyah; Nur Ahmad; Satrya Yudha Prastya; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Global tourism has shifted from sightseeing toward experiential tourism emphasizing educational, emotional, and sensory dimensions. Specific Background Within experience-based coffee destinations like Cikole Luwak Coffee, physical environment attributes and frontline staff interactions function as primary determiners of visitor experiences. Knowledge Gap However, qualitative research examining relational marketing through education-driven personal selling and natural servicescapes in premium coffee tourism remains scarce. Aims This descriptive qualitative study analyzes how educational personal selling strategies and natural servicescape elements contribute to customer satisfaction. Results Utilizing in-depth interviews with seven purposively selected informants, non-participant observation, and digital review analysis, findings indicate that structured product education transforms consumer perception from price skepticism into value-based appreciation. Simultaneously, highland pine forest surroundings create atmospheric sensory immersion, yielding a synergistic interaction that triggers dual cognitive and affective satisfaction. Novelty This study reveals a non-linear synergy where natural surroundings prime cognitive openness while consultative storytelling deepens physical environment meanings. Implications Practitioners must preserve natural landscape identities and invest in staff storytelling capabilities to construct unreplicable experiential competitive advantages. Highlights: Staff product demonstrations shift visitor evaluation from expensive commodity perceptions to high-value experiential learning. Mountainous pine atmospheres provide sensory immersion that prepares visitors psychologically for narrative reception. Combining consultative employee guidance with forest surroundings yields dual cognitive and affective fulfillment. Keywords: Personal Selling, Servicescape, Customer Satisfaction, Educational Tourism, Experiential Marketing